Phytochemical screening and antioxidant activity of unripe canvedish and dream banana (Musa sp.) fruits peels / Nur Nadirah Rodzali, Saiyidah Nafisah Hashim and Muhammad Syamil Mohd Suib - Rodzali, Nur Nadirah; Hashim, Saiyidah Nafisah; Mohd Suib, Muhammad Syamil (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Banana fruit which belongs to the family Musaceae is one of the most widely distributed and consumed fruit in the world especially in tropical and subtropical countries. People only consume the banana’s pulp and dump its peel as solid waste. This gives a very serious agricultural waste disposal and eventually cause environmental problems that keep worsen each day. Thus, this study concern on the phytochemical content and the antioxidant in peel extracts of unripe Cavendish and Dream banana. The dried peels of banana fruit were grinded and extracted by using ethanol as the extraction solvent. The percentage yield of the ethanol extract of unripe Cavendish and Dream banana fruit peels were 17.765 % and 17.081 % respectively. The banana peel extracts were screened for the presence of bioactive compounds which showed the presence of phenols, flavonoids and tannins. Antioxidant activity of the banana peel extracts was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay. The concentration of the peel extracts required for 50 % inhibition of DPPH radical scavenging activity ( ) were recorded at 90.28 μg/ml for Cavendish and 113.09 μg/ml for Dream banana. The extracts of both banana peels definitely showed potential as a sources of natural antioxidant.